Analysis of voltage sag severity caused by fault in power system network / Ng Guan Qun - Ng, Guan Qun (2021)
Power quality issues have become more important to the industry as the impacts created such as plant downtime, production waste, and shorten equipment lifespan are not only caused the financial loss to the industry but also reduce their competitiveness in the market. Besides that, due to the industrial revolution, manufacturing is moving forward to automation, robotics technology, and advance digital technology to have better collaboration, control, and understanding of each operation across all the departments, vendors, products, and people. Therefore, high quality and high-reliability power supply are required in the industry due to the sensitiveness of that electronic equipment especially for the industries such as semiconductor, electronic, computer, and business. As the voltage sag is one of the biggest power quality issues faced by the industry. This study, therefore, aims to analyze the voltage sag severity by a fault in a power system network. An IEEE 14 bus distribution system network will be modeled, and the fault would be applied into the system network and simulated by Power world software. The result of the voltage sag will be recorded and analyzed. Finally, to choose the best location which has the lesser impact of voltage sag when the faults occurred to build a semiconductor manufacturing factory.